Collective Forgetting in a Changing Organization: When memories become unusable and uprooted. Issue 4 (April 2020) - Foroughi, Hamid; Al-Amoudi, Ismael
How is collective remembering inhibited by organizational changes which were not intended to manipulate it? And how does collective forgetting affect workers' power and sense of identity? We rely on an ethnographic study of a charitable organization that went through recent organizational changes to study two processes constitutive of collective forgetting. The first process consists in the past becoming unusable because once-useful memories lost their practical usefulness for participants' new activities. The second process consists in the past becoming uprooted because the social relations through which memories used to be shared had changed beyond recognition. Our findings provide insights into the organizational processes through which memories cease to circulate. They also help understand the complex relations between memory, power relations and participants' sense of identity.